Advancement of Ag–Graphene Based Nanocomposites: An Overview of Synthesis and Its Applications - He, Kai; Zeng, Zhuotong; Chen, Anwei; Zeng, Guangming; Xiao, Rong; Xu, Piao; Huang, Zhenzhen; Shi, Jiangbo; Hu, Liang; Chen, Guiqiu (Small (Weinheim an der Bergstrasse, Germany), 2018)
Graphene has been employed as an excellent support for metal nanomaterials because of its unique structural and physicochemical properties. Silver nanoparticles (AgNPs) with exceptional properties have received considerable attention in various fields; however, particle aggregation limits its application. Therefore, the combination of AgNPs and graphene based nanocomposites (Ag–graphene based nanocomposites) has been widely explored to improve their properties and applications. Excitingly, enhanced antimicrobial, catalytic, and surface enhanced Raman scattering properties are obtained after their combination. In order to have a comprehensive knowledge of these nanocomposites, this Review highlights the chemical and biological synthesis of Ag–graphene nanocomposites. In particular, their applications as antimicrobial agents, catalysts, and sensors in biomedicine, agricultural protection, and environmental remediation and detection are covered. Meanwhile, the factors that influence the synthesis and applications are also briefly discussed. Furthermore, several important issues on the challenges and new directions are also provided for further development of these nanocomposites. Ag–graphene based nanocomposites exhibit great application potential in various fields such as antimicrobial agents, catalysts, and sensors due to the excellent properties. The shape and size of AgNPs on graphene sheets can be tuned with suitable methods for special application. The influence factors and mechanisms are discussed for enhancing the application performance.